Getting the second appointment: - Parinello, Anthony (John Wiley, 2004)
Tony Parinello has done it again! Another original book full of practical examples, useful step-by-step strategies, and compelling insights to help salespeople be more successful. This book has a wonderful mix of practical examples and interconnected sales principles drawn from the author’s extensive experience in the sales profession that anyone can relate to and immediately apply to their sales approach